Entanglement and exotic superfluidity in spin-imbalanced lattices - Franca, V. V. [UNESP] (Elsevier B.V., 2017)
We investigate the properties of entanglement in one-dimensional fermionic lattices at the Fulde-Ferrell-Larkin-Ovchinnikov (FFLO) superfluid regime. By analyzing occupation probabilities, which are concepts closely related to FFLO and entanglement, we obtain approximate analytical expressions for the spin-flip processes at the FFLO regime. We also apply density matrix renormalization group calculations to obtain the exact ground-state entanglement of the system in superfluid and non-superfluid regimes. Our results reveal a breaking pairs avalanche appearing precisely at the FFLO-normal phase transition. We find that entanglement is non-monotonic in superfluid regimes, feature that could be used as a signature of exotic superfluidity. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Entanglement; FFLO superfluidity; Fermionic lattices; Spin-imbalanced systems